Investigating the Role of Governmental Factors Affecting Social Capital (Case Study: Iraqi Kurdistan) - Khayati, Chiman (Technium Sustainability, 2021)
Social capital is a latent wealth and property arising from a society’s members’ mental and psychological readiness to give up personal interests and engage in collective action. Social capital is a form of capital that potentially exists in all human societies. For flourishing and actualizing social capital, factors must be transformed, and special conditions must be satisfied that are seldom and difficult to meet. This study aimed to investigate the factors affecting the strengthening of social capital through the role of government. The study was applied research, and in terms of data collection method, it was a descriptive correlational study. The statistical population of the study was the citizens of Iraqi Kurdistan in 2020. One thousand subjects were selected using the convenience sampling method. The data collection tool was a researcher-made questionnaire. Content validity and measurement model results were used to evaluate the validity and reliability of measurement tools. The questionnaires’ validity and reliability results were confirmed. Structural equation modeling through Smart PLS 3 was used for data analysis. The hypothesis testing results showed that the economy, geography and environment, and culture and society would strengthen social capital through government. According to the value obtained for the model fit index, 0.54, the overall model’s goodness of fit was confirmed.